(untitled) (Spectrum of Humanities and Social Sciences, 2025)
Tourism has emerged as an essential driver of economic growth in Nepal. This study aims to analyze the economic effect of tourism on Nepalese economy focusing on its impact on foreign exchange earnings and GDP contribution. It examines the trends in total number of tourist arrivals and the average duration of their stay from 2000 to 2022. For this, Correlation analysis is used to check the association among the variables such as the total number of tourist arrivals, the average duration of their stay, foreign exchange earnings, and contribution to GDP. Linear regression has been applied to assess the economic effect of tourism on Nepalese economy. The result reveals that the total number of tourist arrivals and average duration of their stay are positively associated with foreign exchange earnings and contribution to GDP in Nepalese economy. This indicates that the tourism sector has a significant impact on the Nepalese economy. Based on these findings, the study suggests that policymakers should prioritize the tourism industry to maximize its economic potential and foster sustainable growth in Nepal.